Tracing carriage, acquisition, and transmission of ESBL-producing Escherichia coli over two years in a tertiary care hospital - Minh Ngoc Nguyen; Beryl Primrose Gladstone; Giulia De Angelis; Michael Biggel; Basil Britto Xavier; Christine Lammens; Qiang Lin; Sandra Van Puyvelde; Herman Goossens; Samir Kumar-Singh; Youri Glupczynski; Yehuda Carmeli; et al. (Genome Medicine)
Abstract Background The impact of community carriage on the influx of extended-spectrum beta-lactamase-producing Enterobacterales (ESBL-E) into hospitals remains understudied. In this prospective 2-year single-centre study, we investigate the community ESBL-E influx and trace the colonisation, nosocomial acquisition, transmission, and infection dynamics of ESBL-producing Escherichia coli (ESBL-Ec) in non-ICU wards at a tertiary care hospital. Methods This study reports primary and post hoc outcomes of the clinical trial NCT01208519 in which hospitalised patients were screened for rectal carriage of ESBL-E. ESBL-Ec isolates from ≈50% of carriers, including all patients who developed infections, were sequenced and genotyped. Endogenous infection was defined as infection by the same strain (< 10 SNPs distance) as colonizing strain. Results Of 3703 screened patients, 456 (12.3%) were ESBL-positive-at-admission (PA-ESBL). Of the 2268 ESBL-negative-at-admission (NA-ESBL) patients with follow-up samples, 240 (10.6%) acquired ESBL-E (HA-ESBL), with an incidence density rate of 7.96 cases/1000 patient-day, notably higher in patients receiving antibiotics (P < 0.001). PA- and HA-ESBL patients developed significantly more ESBL-E infections than ESBL-free patients (P < 0.001). Sequenced ESBL-Ec showed high clonal diversity dominated by the multidrug-resistant and highly virulent ST131 clade, C2/H30-Rx. Among ESBL-Ec infections, 60% (18/30) were endogenous. Direct between-patients transmission clusters (n = 21) involved 23.9% (48/201) of patients and 23.0% (84/366) of ESBL-Ec isolates. Conclusions Our data show a high prevalence of nosocomial acquisition of ESBL-E in a non-ICU setting. The study provides genomic evidence that the endogenous reservoir is the main driver of ESBL-Ec infections underscoring the need for wide implementation of antibiotic stewardship programmes to reduce antibiotic pressure.